English As A Second Language Acquisition From School Activities and Online Video Games - Auliya Rohmah, Nurul (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
Psycholinguistics is the study of mental processes involved in producing and understanding language, as well as the mechanisms through which humans acquire it. Second Language Acquisition (SLA) examines how individuals learn a language other than their mother tongue. In this context, a second language (L2) refers to any non-primary or additional language, regardless of its numerical order of acquisition. This study investigates how English, as a second language, is acquired through elementary school activities and online video games, applying Stephen Krashen's theory of SLA. Using a descriptive qualitative research method, data were collected through a phased interview process with 6th-grade elementary students, aged 12. The findings reveal that the respondents acquired 127 English vocabulary items and sentences, primarily from dominant vocabulary used in these two contexts. The results highlight how engagement in both formal educational settings and interactive gaming environments contributes to vocabulary acquisition, underscoring the practical application of Krashen's theory in varied learning environments. Abstrak Psikolinguistik adalah studi tentang proses mental yang terlibat dalam memproduksi dan memahami bahasa, serta mekanisme yang digunakan manusia untuk memperoleh bahasa. Akuisisi Bahasa Kedua (Second Language Acquisition/SLA) mempelajari bagaimana individu mempelajari bahasa selain bahasa ibu mereka. Dalam konteks ini, bahasa kedua (L2) mengacu pada bahasa non-primer atau tambahan, tanpa memandang urutan akuisisinya. Penelitian ini mengkaji bagaimana bahasa Inggris sebagai bahasa kedua diperoleh melalui kegiatan di sekolah dasar dan video game online, dengan menerapkan teori SLA dari Stephen Krashen. Menggunakan metode penelitian kualitatif deskriptif, data dikumpulkan melalui proses wawancara bertahap dengan siswa kelas 6 SD yang berusia 12 tahun. Temuan penelitian ini mengungkapkan bahwa responden memperoleh 127 kosakata dan kalimat bahasa Inggris, terutama dari kosakata dominan yang digunakan dalam dua konteks tersebut. Hasil ini menyoroti bagaimana keterlibatan dalam lingkungan pendidikan formal dan lingkungan permainan interaktif berkontribusi terhadap perolehan kosakata, menggarisbawahi penerapan praktis teori Krashen dalam lingkungan belajar yang bervariasi. Kata Kunci: psikolinguistik, pemerolehan bahasa kedua, siswa, kegiatan sekolah, online video games.